Study on thermal model for calculating transformer hot Spot temperature - Ramadan Dofan, Jamal Ali (2011)
A power transformer is a static piece of apparatus with two or more windings which, by electromagnetic induction, transforms a system of alternating voltage and current into another system of voltage and current usually of different values and at same frequency for the purpose of transmitting electrical power. The hot spot temperature depends on instantaneous load and ambient temperature, winding design and also cooling model. There are two possible methods for hotspot temperature determination. The first method is to measure the hot spot temperature using a fiber optic, and other is to calculation the hotspot temperature using transformer thermal models. It was noticed that the hot spot temperature rise over top oil temperature due to load changes is a function depending on time as well as the transformer loading (overshoot time dependent function). It has also been noticed that the top oil temperature time constant is shorter than the time constant suggested by the present IEC loading guide, especially in cases where the oil is guided through the windings in a zigzag pattern for the ONAN and ONAF cooling modes. This results in winding hottest spot temperatures higher than those predicted by the loading guides during transient states after the load current increases, before the corresponding steady states have been reached. This thesis presents more accurate temperature calculation methods taking into account the findings mentioned above. The models are based on heat transfer theory, application of the lumped capacitance method, the thermal-electrical analogy and definition of nonlinear thermal resistances at different locations within a power transformer. The methods presented in this thesis take into account all oil physical parameters change and loss variation with temperature. In addition, the proposed equations are used to estimate the equivalent thermal capacitances of the transformer oil for different transformer designs and winding-oil circulations. The models are validated using experimental results, which have been obtained from the normal heat run test performed by the transformer manufacturer at varying load current on a 250-MVA-ONAFcooled unit, a 400-MVA-ONAF-cooled unit and a 2500-KVA-ONAN-cooled unit. The results are also compared with the IEC 60076-7:2005 loading guide method.